Raising the bar in sports performance research - Abt, G.; Jobson, S.; Morin, J.-B.; Passfield, L.; Sampaio, J.; Sunderland, C.; Twist, C. (Journal of Sports Sciences, 2022)
The number of original manuscripts submitted to the Sports Performance section of the Journal of Sports Sciences increased 34% between 2017 and 2020 (637 vs 854). There are many factors that could be contributing to this rise in submissions, including an increase in the popularity of the Journal of Sports Sciences, "publish or perish" pressure (Brischoux & Angelier, 2015), increased data availability through routine monitoring of athletes (Robertson, 2020), perverse incentives, metrification, and hyper-competition that drives academics and researchers to prioritise quantity over quality (Edwards & Roy, 2017; Moore et al., 2017). The rise in submissions to the Sports Performance section means that the bar has raised for getting published. Unfortunately, the space we have within the Journal is not unlimited, and that space is not being increased by the publisher to accommodate the increase in submissions. We also have a dearth of reviewers, which is exacerbated by some researchers wanting their own papers to receive high-quality reviews but unfortunately not willing to review themselves (Stafford, 2018). The bar to publication has also been raised by the emergence of Open Science (Munafò et al., 2017), a movement that comprises both principles (e.g., transparency, reuse, participation, accountability) and practices (e.g., open publications, data-sharing, citizen science; National Academies of Sciences Engineering and Medicine, 2018). Practices aimed at increasing the methodological rigour of scientific studies that have emerged, such as pre-registration and, more recently, Registered Reports (Abt et al., 2021b; Caldwell et al., 2020), are now offered as submission types in the Journal of Sports Sciences. Given this background, we now set out what we are looking for in manuscripts submitted to the Sports Performance section.